Проблемы семейно-брачных отношений у казахов (по этнографическим материалам Южного Казахстана) (Вестник КазНУ. Серия историческая, 2023)
Abstract. This article defines the role of marriage and family in Kazakhstan. At all times, the issues of family and marriage were of concern to both society and the state. It is known that the family is the most important core of society, being part of social institution. Children and teenagers are socialized to traditional values and stereotypes in the family, including respect for old people, a sense of patriotism for their homeland. It is no coincidence, that succesful moral, socio-economic development largely influences on the stability of marriage. In today's market times, the stability of the state directly depends on the stability of family. The article shows the factors influencing on the stability of family. The structure of the family, control in the family, interfamily relations, the upbringing of children, the rational use of free time affect the marriage stability. Understanding these circumstances in ethnological aspect in the future will help to solve many problems related not only to the full functioning of family life of young and middle generation, but also to ensure the normal, reproductive, communicative and economic functioning of family.       Key words: state, society, family, marriage, stability, etiquette, bringing up children.